In-plane excitation of thin silicon cantilevers using piezoelectric thin films - Leighton, Glenn J. T.; Kirby, Paul B.; Fox, Colin H. J. (American Institute of Physics (AIP), 2007)
This paper deals with the actuation of in-plane and out-of-plane motions of silicon cantilevers, using a single thin film of lead zirconate titanate with a divided electrode configuration. In-plane actuation is demonstrated practically, and excellent agreement is obtained between theoretically predicted and experimentally measured resonant amplitudes, for the fundamental out-of-plane and in-plane modes of vibration of the fabricated test cantilevers.